Immunoproteomic to Analysis the Pathogenicity Factors in Leukopenia Caused by Klebsiella Pneumonia Bacteremia - Liu, Haiyan (Public Library of Science, 2014)
Incidences of leukopenia caused by bacteremia have increased significantly and it is associated with prolonged hospital stay and increased cost. Immunoproteomic is a promising method to identify pathogenicity factors of different diseases. In the present study, we used immunoproteomic to analysis the pathogenicity factors in leukopenia caused by Klebsiella Pneumonia bacteremia. Approximately 40 protein spots localized in the 4 to 7 pI range were detected on two-dimensional electrophoresis gels, and 6 differentially expressed protein spots between 10 and 170 kDa were identified. Pathogenicity factors including S-adenosylmethionine synthetase, pyruvate dehydrogenase, glutathione synthetase, UDP-galactose-4-epimerase, acetate kinase A and elongation factor tu (EF-Tu). In validation of the pathogenicity factor, we used western blotting to show that Klebsiella pneumonia had higher (EF-Tu) expression when they accompanied by leukopenia rather than leukocytosis. Thus, we report 6 pathogenicity factors of leukopenia caused by Klebsiella pneumonia bacteremia, including 5 housekeeping enzymes and EF-Tu. We suggest EF-Tu could be a potential pathogenicity factor for leukopenia caused by Klebsiella pneumonia.